The effect of nevirapine vs efavirenz containing regimens on clinical outcomes among HIV patients on ART: a comparative study - Rajput, Jeetam Singh; Mathur, Manoj Kumar; Chaurasia, Ajeet Kumar; Singh, Smriti; Tiwari, Alankar (International Journal of Advances in Medicine, 2017)
Background: The present study has been conducted to compare regimens containing either of nevirapine (NVP) and efavirenz (EFV) and two or more nucleoside reverse transcriptase inhibitors (NRTIs) among HIV infected patients in respect to clinical outcome and to compare incidence of opportunistic infections among these patients. Methods: This study was an observational study conducted at a tertiary care centre over 105 patients, who were evenly matched and received three antiretroviral drug one of the drug was either nevirapine (NVP) or efavirenz (EFV) and these patients were followed up for 6 months for occurrence of any opportunistic infections during these 6 months. Results: 105 patients were followed for 6 months, the maximum incidence of opportunistic infection (OI’s) was found among patients who were on ZLN (zidovudine, lamivudine, nevirapine) regime i.e. 60% followed by patients who changed their regime from ZLN to TLE i.e. 36.5%, while the least incidence of OI’s was noted among the patients who were on TLE (tenofovir, lamivudine, efavirenz) regime i.e. 28.5%. These differences were found to be statistically significant (p<0.05). Conclusions: EFV containing antiretroviral regimen was associated with superior clinical outcome than NVP containing regimen.